2016
DOI: 10.1016/j.chb.2016.05.068
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the effects of emotion management on time and self-management in computer-based learning

Abstract: Emotional learning involves the acquisition of skills to recognize and manage emotions, develop care and concern for others, make responsible decisions, establish positive relationships, and handle challenging situations effectively. Time is an important variable in learning context and especially in the analysis of teaching-learning processes that take place in collaborative learning, whereas time management is crucial for effective learning. The aim of this work has been to analyze the effects of emotion man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 68 publications
4
22
0
5
Order By: Relevance
“…Studies found and reported in the literature section of this study minimally examined the COVID-19 lockdown impact on students' psychological readiness. Students' emotions play an indispensable role in education [27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Studies found and reported in the literature section of this study minimally examined the COVID-19 lockdown impact on students' psychological readiness. Students' emotions play an indispensable role in education [27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Para auxiliar os estudantes a lidarem com a confusão a fim de desencadear o engajamento e evitar a resistência ao processo de aprendizagem, diversas pesquisas apontam a importância da regulação emocional, particularmente, da confusão, durante o ensino com o suporte computacional (Arguedas, Daradoumis, & Xhafa, 2016). A regulação emocional refere-se à capacidade de gerenciar o estado emocional por meio do monitoramento, da avaliação e da modificação das respostas emocionais (Thompson, 1991) com objetivo de promover bem estar pessoal.…”
Section: Introductionunclassified
“…Emotion management has gained increasing attention in recent years (Arguedas et al, 2016;Bellocchi, 2019;Logan, 2018). Emotion management may be defined as being aware of which emotions are being experienced at the moment and then understanding, regulating, and working effectively with those emotions.…”
Section: Introductionmentioning
confidence: 99%